Regulating Market Entry of Low-Cost Private Schools in Sub-Saharan Africa : Towards a Theory of Private Education Regulation - Baum, Donald R.; Cooper, Rachel; Lusk-Stover, Oni (Elsevier, 2018)
This study provides a comparative assessment of policies governing private schools in twenty countries in Sub-Saharan Africa. Findings suggest that current regulatory systems are failing to adequately address the negative externalities and failures of private schooling markets. Insufficient capacity on the part of governments is a contributor to uneven policy implementation and creates opportunities for rent-seeking and corruption. Onerous market entry regulations offer constraints on the growth of official private education markets, but facilitate growth in unofficial markets if demand for education is not being fully met by the supply of government service provision, restricting the government’s ability to provide adequate oversight of private providers.